2017
DOI: 10.1002/2016je005244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an impact origin for Mercury's high‐magnesium region

Abstract: During its four years in orbit around Mercury, the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft's X‐ray Spectrometer revealed a large geochemical terrane in the northern hemisphere that hosts the highest Mg/Si, S/Si, Ca/Si, and Fe/Si and lowest Al/Si ratios on the planet. Correlations with low topography, thin crust, and a sharp northern topographic boundary led to the proposal that this high‐Mg region is the remnant of an ancient, highly degraded impact basin. Here we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 86 publications
(192 reference statements)
1
26
0
Order By: Relevance
“…For example, a ~200-kmdiameter region centered close to the crater Jobim (32.5°N, -67°E) has substantially lower Mg/Si and higher Al/Si than the HMR as a whole. This feature also corresponds to a topographic high, and thicker crust, than the rest of the HMR (Frank et al, 2017). Moreover, our maps reveal clear latitudinal variations in chemical composition across the HMR.…”
Section: High-mg Regionsupporting
confidence: 55%
See 1 more Smart Citation
“…For example, a ~200-kmdiameter region centered close to the crater Jobim (32.5°N, -67°E) has substantially lower Mg/Si and higher Al/Si than the HMR as a whole. This feature also corresponds to a topographic high, and thicker crust, than the rest of the HMR (Frank et al, 2017). Moreover, our maps reveal clear latitudinal variations in chemical composition across the HMR.…”
Section: High-mg Regionsupporting
confidence: 55%
“…2-4 and first identified by W15. A detailed investigation of the HMR and its possible origins was conducted by Frank et al (2017), who used the maps reported here in their analysis. The higher-resolution maps presented here clarify compositional heterogeneity across the HMR that was hinted at in the maps of W15 (see Fig.…”
Section: High-mg Regionmentioning
confidence: 99%
“…Craters with the strongest 600-nm band depth-Basho and Rachmaninoff-may have >4 wt%, perhaps up to 4.5 wt% excess carbon. Interestingly, they also found that the region of intercrater plains near 270°E, near the large, Mg-rich anomaly identified by the X-ray spectrometer on MESSENGER (Frank et al, 2017;Weider et al, 2015) is almost devoid of LRM. Leeburn et al (2017) examined over 1,000 craters >20 km in diameter on a global scale to classify whether or not, based on an LRM threshold map, they excavated LRM.…”
Section: Geophysical Research Lettersmentioning
confidence: 93%
“…They showed that for small-to moderate-sized craters, estimated to excavate material from depths up to 15 km, the median excavation depth for LRM was 4.3 km, whereas that for non-LRM materials was 3.1 km. Interestingly, they also found that the region of intercrater plains near 270°E, near the large, Mg-rich anomaly identified by the X-ray spectrometer on MESSENGER (Frank et al, 2017;Weider et al, 2015) is almost devoid of LRM. In contrast, they examined a region that coincides with R3 in this work and found that LRM-rich craters dominated the region as a whole, with a median excavation depth of 6.3 km (Leeburn et al, 2017).…”
Section: Geophysical Research Lettersmentioning
confidence: 93%
“…The age estimation of the emplacement of the interior plains of the caloris basin is around 3.7 Gyr ago (Fassett et al, ). The HMR region is mostly covered by intercrater plains, possesses a full range of crater densities, and its northwestern part is bounded by lower Mg/Si smooth plains (Frank et al, ) that indicates that the HMR region predates the volcanism associated with the NP. The HMR is probably one of the most ancient surfaces of the planet and could have been emplaced prior to or contemporaneous to the IcP‐HcT.…”
Section: Discussionmentioning
confidence: 99%